Crafts as an example of active and productive aging: profiles of artisans and family transmission in a UNESCO Creative City of Crafts and Folk Art - Igreja, Sandra; Teles, Soraia; Paúl, Constança (Frontiers in Psychology, 2025)
In light of global demographic changes, sustainable solutions promoting active and healthy aging are crucial. Crafts, besides preserving cultural heritage, offer a meaningful occupation. Barcelos (Portugal), a UNESCO Creative City of Crafts and Folk Art, stands out for its strong craft activity, predominantly by older artisans. However, studies addressing their profiles, family transmission dynamics, and craftsmanship as an example of active aging are lacking, which this study aims to explore. An observational cross-sectional study was conducted, with primary data collection through on-site questionnaires at the ateliers. A non-probability sample of older artisans (aged 55 or older) from different craft sectors was recruited. The participants (n = 55) were mostly male (60%, n = 33), with a mean age of 67.5 years (SD = 8.02) and 6.4 years of formal education (SD = 3.32). They worked across eight craft and folk art sectors, with the Imagery sector being the most represented (52.7%). A weekly average of 51 h (SD = 17.05) dedicated to the activity was reported. Most participants started in crafts before the age of 20 (76.3%; n = 42), and 60% (n = 33) continued the craft activity after retirement. The activity was transmitted by family members from previous generations (63.6%; n = 35), and 70.9% (n = 39) had family members involved in the activity; among those practicing the craft with other or same-generation relatives (n = 34), 58.8% engaged in the craft with collateral or affinal relatives. Most artisans reported that the activity began in the family three or more generations ago and dates to the 19th century. This study makes an original contribution to gerontological research, highlighting craftsmanship as an example of active and productive aging. It informs public policy discussions supporting older artisans, fostering intergenerational craft transmission, family business sustainability, and cultural heritage preservation.